Preparation method of perovskite quantum dot adhesive film

By preparing perovskite quantum dots under the protection of inert gas and mixing them with rubber particles, the problem of poor stability of perovskite quantum dot film under high temperature, humidity and UV irradiation is solved, and high stability and high efficiency light are achieved Electroluminescent perovskite quantum dispensing film.

CN119505722APending Publication Date: 2025-02-25SHANGHAI XIANGUANG APPLIED MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560108.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing perovskite quantum dispensing films have poor stability under high temperature, humidity and UV irradiation, resulting in limited application efficiency in the field of photovoltaics.

Method used

Using a method of preparing perovskite quantum dispensing film, the precursor solution and solution are prepared under the protection of inert gas, and the reaction conditions are controlled to generate high-stability perovskite quantum dots, and then these quantum dots are combined with blank gum particles. Mix, melt extrusion and granulation to form a stable adhesive film.

Benefits of technology

After the environmental stability test of the prepared perovskite quantum dispensing film, the photoluminescent quantum yield (PLQY) attenuation is less than 7%, which significantly improves its stability and has good hydrothermal and light stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117649110000071
    Figure BDA0005117649110000071
  • Figure BDA0005117649110000072
    Figure BDA0005117649110000072
Patent Text Reader

Abstract

The invention belongs to the field of film preparation, and particularly relates to a preparation method of a perovskite quantum dot adhesive film. Comprising the following steps: 1.1) dissolving Cs2CO3 in a mixed solvent a, and preparing a precursor solution A; 1.2) dissolving PbX2 and transition metal chloride in a mixed solvent a, and adding a silane coupling agent to prepare a solution B; and 1.3) adding the solution A into the solution B, and carrying out a reaction. Compared with the prior art, the adhesive film has the advantages that the attenuation of the photoluminescence quantum yield (PLQY) is less than 7% after the adhesive film is subjected to an environmental stability test, and the adhesive film has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thin film material preparation, and in particular relates to a method for preparing a perovskite quantum dot adhesive film. Background Art

[0002] In the current photovoltaic power generation industry, P-type silicon power generation technology, represented by emitter passivation and rear contact (PERC) technology, has gradually reached its efficiency limit (-24.5%). Compared with P-type silicon, N-type silicon has a longer carrier lifetime, and photovoltaic cells based on N-type silicon have higher photoelectric conversion efficiency. Heterojunction (HJT or HIT) technology, as a representative technology for N-type silicon power generation, has a maximum efficiency of 27.5%. However, the absorption of ultraviolet light by the TCO layer and the amorphous silicon passivation layer results in a low response of HJT cells to ultraviolet and short-wave radiation, making their current lower than the PERC current.

[0003] Due to the long carrier lifetime of N-type silicon, HJT cells have higher theoretical conversion efficiency than PERC cells. However, the absorption of ultraviolet light by the TCO layer and amorphous silicon passivation layer in HJT cells results in a low current. Fluorescence down-conversion technology converts ultraviolet light into visible light that can be efficiently utilized by HJT cells, enhancing the cell's spectral responsivity and further improving its photoelectric conversion efficiency. Perovskite quantum dots, as fluorescence down-conversion materials, offer advantages such as a wide absorption range, high PLQY, and continuously adjustable luminescence. Highly stable perovskite quantum dot films are the foundation and key to improving the cell's photoelectric conversion efficiency.

[0004] CN116693905A discloses a perovskite quantum dot film and its preparation method. The preparation method includes mixing precursor A, precursor B, and precursor X with a matrix resin, and extruding to obtain the perovskite quantum dot film; or, granulating precursor A, precursor B, and precursor X with a matrix resin to obtain masterbatches containing precursor A, precursor B, and precursor X, respectively, mixing the masterbatches, and extruding to obtain the perovskite quantum dot film, and defining extrusion parameters. During the extrusion process, the precursors react to form perovskite quantum dots, which are then grown in situ in the film to obtain the perovskite quantum dot film. However, the perovskite quantum dots prepared by this method have many defects and are limited in their ability to improve the efficiency of solar cells. Currently, perovskite quantum dot films used in silicon-based solar cells often exhibit poor stability for three reasons. First, the preparation of perovskite films into photovoltaic devices requires high-temperature crosslinking, a process performed at temperatures between 140 and 160°C. High temperatures above 100°C damage quantum dots and accelerate ion migration, resulting in poor stability at high temperatures. Second, perovskite quantum dots are sensitive to water and oxygen, and their lattice easily disintegrates upon long-term exposure to high humidity. Third, perovskite quantum dots exhibit poor stability under high-energy UV irradiation. Consequently, conventional perovskite films completely lose their fluorescence after high-temperature lamination, exposure to high-temperature and high-humidity environments, and UV irradiation, resulting in a loss of their down-conversion performance advantage. Therefore, the development of highly stable perovskite quantum dot films is crucial, as they hold great potential for application in the photovoltaic field.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The present invention aims to provide a method for preparing a perovskite quantum dot film. The perovskite quantum dot film prepared by the method of the present invention has a photoluminescence quantum yield (PLQY) attenuation of less than 7% after undergoing an environmental stability test, indicating good stability.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a perovskite quantum dot film includes preparing perovskite quantum dots PeQDs and preparing a film, wherein the process of preparing the perovskite quantum dots PeQDs includes the following steps:

[0009] 1.1) Preparing precursor solution A: Dissolve Cs2CO3 in mixed solvent a, stirring and heating under inert gas protection until it is completely dissolved to obtain precursor solution A;

[0010] 1.2) Preparation of Solution B: Weigh a certain amount of PbX2 and a transition metal chloride, add a certain amount of mixed solvent a, stir and dissolve under inert gas, heat to temperature T1, hold for a period of time t1, then raise the temperature to temperature T2, add a silane coupling agent, hold for a period of time t2, to obtain Solution B;

[0011] 1.3) Preparation of perovskite quantum dots (PeQDs): A certain amount of precursor solution A was added to solution B, reacted for a period of time t3, and then cooled to room temperature. After removal, methyl acetate was added, the mixture was centrifuged, and the perovskite quantum dots (PeQDs) were dissolved in hexane.

[0012] Furthermore, in step 1.2), the usage ratio of PbX2, transition metal chloride and silane coupling agent is (5-8) mmol: (2-5) mmol: (5-10) ml.

[0013] Furthermore, the silane coupling agent is a vinyl silane coupling agent.

[0014] Furthermore, X in PbX2 is Cl, Br or I; and the transition metal chloride is ZnCl2, MnCl2, CdCl2, CoCl2 or CuCl2.

[0015] Furthermore, in step 1.1), the ratio of the amount of Cs2CO3 to the mixed solvent a is (0.03-0.05) mol: (80-150) ml; and the heating is to 120-180°C.

[0016] Furthermore, the mixed solvent a is one or more of octadecene, oleic acid, and oleylamine.

[0017] Furthermore, in step 1.2), the temperature T1 is 100-180°C, preferably 120-160°C; the time t1 is 20-60 min, preferably 30-50 min; the temperature T2 is 140-280°C, preferably 150-250°C; and the time t2 is 20-60 min, preferably 30-50 min.

[0018] Furthermore, in step 1.3), the volume ratio of precursor solution A to solution B is (3-10):(90-97), preferably (5-8):(92-95).

[0019] Furthermore, it is characterized in that the process of preparing the film comprises the following steps:

[0020] 2.1) Perovskite quantum dot colloids: Perovskite quantum dots PeQDs and blank colloids are mixed at a mass ratio of (1.5-3.0): (20-40), melt-extruded, and granulated to obtain perovskite quantum dot colloids;

[0021] 2.2) Preparation of film: Weigh 3-20 parts of perovskite quantum dot colloids, 75-95 parts of blank colloids, 0.1-2 parts of coupling agent, 0.4-2 parts of main cross-linking agent, 0.4-2 parts of auxiliary cross-linking agent, 0.05-0.2 parts of light stabilizer and 0.05-0.2 parts of antioxidant by weight; after mixing evenly, melt extrusion and film formation by cast film method to obtain the perovskite quantum dot film.

[0022] In the present invention, the blank colloid particles are one or both of EVA colloid particles and POE colloid particles.

[0023] The coupling agent includes one or more of vinyl silane coupling agent, epoxy silane coupling agent, alkyl silane coupling agent, amino silane coupling agent, isocyanate silane coupling agent, sulfur-containing silane coupling agent or piperazine silane coupling agent.

[0024] The main cross-linking agent includes one or more of 2-ethylhexyl peroxide tert-butyl carbonate, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, dicumyl peroxide and 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane.

[0025] The auxiliary cross-linking agent includes one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and ethoxylated trimethylolpropane triacrylate.

[0026] The light stabilizer includes one or more of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidinylethanol) succinate, and bis(1,2,2,6,6-pentamethylpiperidinol) sebacate.

[0027] The antioxidant includes one or more of aromatic amine antioxidants, hindered phenol antioxidants and phosphite antioxidants.

[0028] Further,

[0029] In step 2.1), the mixing conditions are: temperature 20-120°C, time 0.2-2h; the melt extrusion conditions are: temperature 50-200°C, time 0.2-2h, speed 20-80rpm; the granulation temperature is 80-150°C;

[0030] In step 2.2), the temperature of the film-forming process by the tape casting method is 70-150° C., and the thickness of the film is 0.2-0.5 mm.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] The perovskite quantum dot adhesive film prepared by the present invention has a photoluminescence quantum yield (PLQY) attenuation of less than 7% after undergoing an environmental stability test, and has good stability. DETAILED DESCRIPTION

[0033] The following are specific embodiments of the present invention. The examples are intended to further describe the present invention rather than to limit the present invention.

[0034] Example 1

[0035] 1. Preparation of Perovskite Quantum Dots PeQDs

[0036] 1.1) Prepare precursor solution A: Dissolve 0.03 mol Cs2CO3 in 80 ml of mixed solvent a (octadecene, oleic acid, and oleylamine in a 1:1:1 volume ratio). Stir continuously and heat to 120°C under inert gas until completely dissolved to obtain precursor solution A.

[0037] 1.2) Preparation of Solution B: Weigh 8 mmol of PbCl₂ and 2 mmol of ZnCl₂, add 80 ml of mixed solvent a (octadecene, oleic acid, and oleylamine in mixed solvent a have a volume ratio of 1:1:1), stir and dissolve under inert gas, and heat to 100°C (T1) for 45 min. Then, raise the temperature to 140°C, add 5 ml of vinyltriisopropoxysilane, and hold for 30 min to obtain Solution B.

[0038] 1.3) Preparation of perovskite quantum dots (PeQDs): 3 ml of precursor solution A was added to 97 ml of solution B, reacted for 10 s, and cooled to room temperature. Methyl acetate was added to the solution, centrifuged three times, and dissolved in hexane to obtain perovskite quantum dots (PeQDs).

[0039] 2. Preparation of film

[0040] 2.1) Perovskite quantum dot colloids: 30 g of perovskite quantum dots PeQDs were mixed with 300 g of EVA colloids at 20°C for 0.2 h, then melt-extruded at 50°C and 20 rpm for 0.2 h, and finally granulated at 80°C to obtain perovskite quantum dot colloids;

[0041] 2.2) Preparation of film: Weigh 30 g of perovskite quantum dot colloid, 75 g of EVA colloid, 0.1 g of γ-aminopropyltriethoxysilane, 0.4 g of tert-butyl peroxide 2-ethylhexyl carbonate, 0.4 g of triallyl isocyanurate, 0.05 g of bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and 0.05 g of N,N'-di(1,4-dimethylpentyl)-p-phenylenediamine; mix them evenly, melt extrude them, and form them into a film by a casting method. The temperature in the casting method is 70°C, and a perovskite quantum dot film with a thickness of 0.2 mm is obtained.

[0042] Example 2

[0043] 1. Preparation of Perovskite Quantum Dots PeQDs

[0044] 1.1) Prepare precursor solution A: Dissolve 0.05 mol Cs2CO3 in 150 ml of mixed solvent a (octadecene, oleic acid, and oleylamine in a 1:1:1 volume ratio). Stir continuously and heat to 180°C under inert gas until completely dissolved, to obtain precursor solution A.

[0045] 1.2) Preparation of Solution B: Weigh 5 mmol of PbBr2 and 5 mmol of MnCl2, add 150 ml of mixed solvent a (octadecene, oleic acid, and oleylamine in mixed solvent a have a volume ratio of 2:1:1), stir and dissolve under inert gas, heat to a temperature T1 of 180°C, hold for 30 min, then raise the temperature to a temperature T2 of 280°C, add 8 ml of vinyltriethoxysilane, and hold for 50 min to obtain Solution B;

[0046] 1.3) Preparation of perovskite quantum dots (PeQDs): 10 ml of precursor solution A was added to 90 ml of solution B, reacted for 60 s, and cooled to room temperature. Methyl acetate was added to the solution, centrifuged three times, and dissolved in hexane to obtain perovskite quantum dots (PeQDs).

[0047] 2. Preparation of film

[0048] 2.1) Perovskite quantum dot colloids: 15 g of perovskite quantum dots PeQDs were mixed with 200 g of POE colloids at 120°C for 2 h, then melt-extruded at 200°C and 80 rpm for 2 h, and finally granulated at 150°C to obtain perovskite quantum dot colloids;

[0049] 2.2) Preparation of film: Weigh 20g of perovskite quantum dot particles and 95g of POE particles, 2g of γ-glycidyloxypropyltrimethoxysilane, 2g of 2,5-dimethyl-2,5-di-tert-butylperoxyhexane, 2g of trimethylolpropane trimethacrylate, 0.2g of poly(4-hydroxy-2,2,6,6-tetramethyl-1-piperidineethanol) succinate and 0.2g of 2,6-di-tert-butyl-4-methylphenol; after mixing evenly, melt-extrude and form a film by cast film method. The temperature in the cast film forming process is 150°C to obtain a perovskite quantum dot film with a film thickness of 0.5mm.

[0050] Example 3

[0051] 1. Preparation of Perovskite Quantum Dots PeQDs

[0052] 1.1) Preparation of precursor solution A: Dissolve 0.04 mol Cs2CO3 in 100 ml of mixed solvent a (octadecene, oleic acid, and oleylamine in a 1:1:1 volume ratio). Heat to 150°C under inert gas with constant stirring until completely dissolved, to obtain precursor solution A.

[0053] 1.2) Preparation of Solution B: Weigh 7 mmol of PbI2 and 3 mmol of CdCl2, add 100 ml of mixed solvent a (the volume ratio of octadecene, oleic acid, and oleylamine in mixed solvent a is 1.5:1:2), stir and dissolve under inert gas, heat to 150°C, hold for 40 min, then raise the temperature to 200°C, add 10 ml of γ-methacryloxypropyltrimethoxysilane, and hold for 40 min to obtain Solution B.

[0054] 1.3) Preparation of perovskite quantum dots (PeQDs): 5 ml of precursor solution A was added to 95 ml of solution B, reacted for 30 seconds, and cooled to room temperature. Methyl acetate was added to the solution, centrifuged three times, and dissolved in hexane to obtain perovskite quantum dots (PeQDs).

[0055] 2. Preparation of film

[0056] 2.1) Perovskite quantum dot colloids: 20 g of perovskite quantum dots PeQDs were mixed with 400 g of EVA colloids at 80°C for 1 h, then melt-extruded at 100°C and 50 rpm for 1 h, and finally granulated at 100°C to obtain perovskite quantum dot colloids;

[0057] 2.2) Preparation of adhesive film: Weigh 10 g of perovskite quantum dot colloid, 80 g of EVA colloid, 1 g of dodecyltrimethoxysilane, 1 g of diisopropylbenzene peroxide, 1 g of trimethylolpropane triacrylate, 0.1 g of bis(1,2,2,6,6-pentamethylpiperidinol)sebacate and 0.1 g of tris[2,4-di-tert-butylphenyl]phosphite; mix them evenly, melt extrude them, and form them into a film by a casting method. The temperature in the casting method is 100°C to obtain a perovskite quantum dot film with a thickness of 0.3 mm.

[0058] Example 4

[0059] This embodiment is the same as embodiment 1, except that the transition metal chloride added in step 1.2) is CoCl2.

[0060] Example 5

[0061] This embodiment is the same as embodiment 1, except that the transition metal chloride added in step 1.2) is CuCl2.

[0062] Comparative Example 1

[0063] This comparative example is the same as Example 1, except that no vinyl silane coupling agent is added in step 1.2).

[0064] Test Example 1

[0065] This test example investigates the stability of the perovskite quantum dot films prepared in various embodiments and comparative examples of the present invention.

[0066] Detection method: After stacking photovoltaic glass, perovskite quantum dot film, and photovoltaic glass in order on the photovoltaic glass, put it into a vacuum laminator, evacuate for 10 minutes, heat it to 145°C, and laminate it under a pressure of 25 MPa to obtain a photovoltaic module.

[0067] The perovskite quantum dot films prepared in each embodiment and comparative example were used as intermediate quantum dot film layers, and laminated according to the above method to obtain photovoltaic modules. The thermal conductivity of each laminated module was measured in a high temperature and high humidity test environment (85°C temperature and 85% humidity) and at 100W / m 2 The photoluminescence quantum yields of the samples were irradiated under UVA+UVB ultraviolet light for different time periods and compared to obtain the following test data:

[0068] The test results are shown in Table 1 and Table 2:

[0069] Table 1. Lamination stability at 145°C, 85°C, 85% RH

[0070]

[0071] Table 2, lamination at 145°C, at 100W / m 2 Stability under UVA+UVB ultraviolet light for 600h

[0072]

[0073] From the photoluminescence quantum yield results in Table 1 and Table 2, it can be seen that, on the one hand, the perovskite quantum dot film prepared by adding a vinyl silane coupling agent in the present invention has good stability after high-temperature lamination, and the quantum yield after lamination can still be maintained at more than 94% of the initial quantum yield after high-temperature and high-humidity testing, while the quantum yield of the perovskite quantum dot film without adding a vinyl silane coupling agent is reduced to 51.6% of the initial value after lamination after 1000h of high-temperature and high-humidity testing, which shows that the perovskite quantum dot film with the addition of a vinyl silane coupling agent has good hydrothermal stability; on the other hand, the laminated perovskite film has a good thermal stability at 100W / m 2 The quantum yield of the product remained above 94% after irradiation with UVA+UVB lamp for 600 hours, indicating good photostability.

Claims

1. A method for preparing a perovskite quantum dot film, comprising preparing perovskite quantum dots PeQDs and preparing a film, wherein the process of preparing perovskite quantum dots PeQDs comprises the following steps: 1.1) Preparing precursor solution A: dissolving Cs2CO3 in mixed solvent a, stirring and heating continuously under the protection of inert gas to completely dissolve it, thereby obtaining precursor solution A; 1.2) preparing solution B: weighing a certain amount of PbX2 and transition metal chloride, adding a certain amount of mixed solvent a, stirring and dissolving under the protection of inert gas and heating to temperature T1, maintaining for a period of time t1, then heating to temperature T2, adding silane coupling agent, maintaining for a period of time t2, to obtain solution B; 1.3) Preparation of perovskite quantum dots PeQDs: a certain amount of precursor solution A is added to solution B, and the solution is cooled to room temperature after reaction; methyl acetate is added after taking out, centrifuged, and the solution is dissolved with hexane to obtain perovskite quantum dots PeQDs.

2. The preparation method according to claim 1, characterized in that: In step 1.2), the usage ratio of PbX2, transition metal chloride and silane coupling agent is (5-8) mmol: (2-5) mmol: (5-10) ml.

3. The preparation method according to claim 2, characterized in that: The silane coupling agent is a vinyl silane coupling agent.

4. The preparation method according to claim 3, characterized in that: In PbX2, X is Cl, Br or I; and the transition metal chloride is ZnCl2, MnCl2, CdCl2, CoCl2 or CuCl2.

5. The preparation method according to claim 1, characterized in that: In step 1.1), the usage ratio of Cs2CO3 to mixed solvent a is (0.03-0.05) mol: (80-150) ml; and the heating is to 120-180°C.

6. The preparation method according to claim 5, characterized in that: The mixed solvent a is one or more of octadecene, oleic acid and oleylamine.

7. The preparation method according to claim 1, characterized in that: In step 1.2), the temperature T1 is 100-180°C, preferably 120-160°C; the time t1 is 20-60 min, preferably 30-50 min; the temperature T2 is 140-280°C, preferably 150-250°C; the time t2 is 20-60 min, preferably 30-50 min.

8. The preparation method according to claim 1, characterized in that: In step 1.3), the volume ratio of precursor solution A to solution B is (3-10):(90-97), preferably (5-8):(92-95); the reaction time is 10-60s.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The process of preparing the film includes the following steps: 2.1) Perovskite quantum dot colloid particles: Perovskite quantum dots PeQDs and blank colloid particles are mixed at a mass ratio of (1.5-3.0): (20-40), and then melt-extruded and granulated to obtain perovskite quantum dot colloid particles; 2.2) Preparation of adhesive film: by weight, weigh 3-20 parts of perovskite quantum dot particles, 75-95 parts of blank particles, 0.1-2 parts of coupling agent, 0.4-2 parts of main cross-linking agent, 0.4-2 parts of auxiliary cross-linking agent, 0.05-0.2 parts of light stabilizer and 0.05-0.2 parts of antioxidant; after mixing evenly, melt extrusion and film formation by cast film method to obtain the perovskite quantum dot adhesive film.

10. The preparation method according to claim 9, characterized in that: In step 2.1), the mixing conditions are: temperature 20-120°C, time 0.2-2h; the melt extrusion conditions are: temperature 50-200°C, time 0.2-2h, speed 20-80rpm; the granulation temperature is 80-150°C; In step 2.2), the temperature of the film-forming process by the casting method is 70-150° C., and the thickness of the film is 0.2-0.5 mm.